LEGAL PROTECTION FOR MSME TRADERS WHO EXPERIENCE A DECLINE IN PURCHASING POWER DUE TO THE IMPACT OF ONLINE SELLING AND BUYING TRANSACTIONS REVIEWED BY JURIDICAL STUDY - Yasmirah Mandasari Saragih; Fahmi Anwar Tanjung; Muhammad Fahmi; M. Fajri Hidayatullah; Alexander (PT. Radja Intercontinental Publishing, 2023)
This article aims to find out how legal protection is for small traders who experience a decrease in purchasing power due to the impact of online buying and selling transactions and how the juridical review of online buying and selling transactions has an impact on the micro-economic sector of society. This writing is motivated by the problems of people who own MSME businesses due to the decline in purchasing power due to changes in digitalization, including in the economic aspect. The research method used is the Normative Juridical method with a descriptive analysis approach. The results of this research are that legal protection for MSMEs is regulated in article 50 letter (h) of Law no. 5 of 1999 and in a juridical study of online buying and selling transactions/electronic transactions only regulates transaction procedures, not comprehensive aspects of problems between sectors of the national economy, but the government must take a stand in combining and providing counseling to the national economic sector in Indonesia and facilitate.